Foreign Direct Investments into Eastern Africa Region: The Infrastructure Development Nexus - Bosire, Eric Mokwaro (International Journal of Economics and Financial Issues, 2020)
Infrastructure development is an essential element in economic growth and development. Good infrastructure fosters low transaction costs hence making production efficient and attracting foreign direct investments. However, there has not been adequate scholarly focus on how infrastructure development can affect the flow of foreign direct investments hence this paper sought to fill this gap. This paper utilized panel data from 12 eastern Africa countries from 2004 through 2017. Data on Infrastructure development variables was obtained from the Africa Development Bank’s, Africa Infrastructure Development Index, that of control variables from the World Development Indicators kept by the World Bank and that of Foreign direct investments from UNCTAD. Due to the presence of heteroscedasticity in sample data, the study opted for a Generalized Least Squares (GLS) estimation method. The study established a significant relationship between infrastructure development and foreign direct investment inflows into the eastern Africa region. However, only Africa Infrastructure Index and Electricity Composite Index were positive while Transport Composite Index, ICT Composite Index and Water Supply and Sanitation Index were negative. Reasons being, Transport, ICT, water and sanitation are considered as social development factors. One of the control variables, total tax and contribution rate was negative indicating a unit increase in tax leads to a decrease in foreign direct investments whereas market size was positive and significant. The study recommends to policy makers to allocate resources into infrastructure development as an enabler of production efficiency, appraise the tax system to ensure a balance is stroked between taxing of investment returns and generating adequate tax revenue from multinationals and enhance its markets through multilateral and preferential trade agreements and regional integration agreements. Keywords: Africa Infrastructure Development Index, Transport Composite Index, Electricity Composite Index, ICT Composite Index, Water Supply and Sanitation Index, Foreign Direct Investments JEL Classifications: C33, F21, H4, R4 DOI: https://doi.org/10.32479/ijefi.10378